Vedibandha (basal mouldings) of Mandaleshwar Mahadev Temple - Temples of India Project Team (Jio Institute, 2024)
Details of the mouldings of the vedibandha (basal mouldings) of the temple. The broad kumbha (pot) moulding consists of a diamond motif band at its centre and a kirtimukha (face of glory) moulding at its base. Most of the plinth’s mouldings are plain.